EVALUATION OF THE IMPLEMENTATION OF JAKARTA SMART CARD PROGRAM IN A PRIVATE SCHOOL IN WEST JAKARTA - Elin DRIANA; Desi MERAWATI; Abd. Rahman A. GHANI (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2018)
In 2012, the Provincial Government of Special Capital Region of Jakarta (DKI) launched the Education Personal Cost Assistance (BBPP) through Jakarta Smart Card (KJP). This program is intended as an effort to help students from less fortunate families to fulfill their 12-year compulsory education. In its implementation, this program faced problems. This research, which was done at SMP Al-Abror, a private junior secondary school in Kembangan Sub-district, West Jakarta in February through November 2017, has the purpose to evaluate the implementation of the KJP program. The evaluation focused on data collection, distribution, usage, and reporting, by implementing the Discrepancy Evaluation Model (DEM). The data were collected through document analysis, observation, interview, and survey which were then analyzed qualitatively and quantitatively based on the type of data. The results of the evaluation show that the data collection process at SMP Al-Abror has been done according to the established procedures and standards and is categorized as good. The distribution of students’ account books and ATM KJP is also categorized as good. The usage and reporting of KJP funds is categorized as very good. However, in its implementation, there are still problems during the data collection stage, especially in the visitation stage due to the lack of time of the home room teachers have. Other than that, there are still infractions that occur including cash withdrawals for unauthorized uses and also students who did not report the uses of the KJP fund.